The relationship between phytoplankton diversity and community function in a coastal lagoon - Duarte, Pedro (2007)
The decrease of biodiversity related to the phenomena of global climate change is stimulating the scientific community towards a better understanding of the relationships between biodiversity and ecosystem functioning. In ecosystems where marked biodiversity changes occur at seasonal time scales, it is easier to relate them with ecosystem functioning. The objective of this work is to analyse the relationship between phytoplankton diversity and primary production in St. André coastal lagoon – SW Portugal. This lagoon is artificially opened to the sea every year in early spring, exhibiting a shift from a marine dominated to a low salinity ecosystem in winter. Data on salinity, temperature, nutrients, phytoplankton species composition, chlorophyll a (Chl a) concentration and primary production were analysed over a year. Modelling studies based on production-irradiance curves were also conducted. A total of 19 taxa were identified among diatoms, dinoflagellates and euglenophyceans, the less abundant group. Lowest diversities (Shannon– Wiener index) were observed just before the opening to the sea. Results show a negative correlation (p<0.05) between diversity and chlorophyll a (Chl a) concentration (0.2–40.3 mg Chl a m-3). Higher Chl a values corresponded to periods when the community was dominated by the dinoflagellate Prorocentrum minimum (>90% of cell abundance) and production was maximal (up to 234.8 mg C m-3 h-1). Maximal photosynthetic rates (Pmax) (2.0–22.5 mg C mg Chl a-1 h-1) were higher under lower Chl a concentrations. The results of this work suggest that decreases in diversity are associated with increases in biomass and production, whereas increases correspond to opposite trends. It is suggested that these trends, contrary to those observed in terrestrial and in some benthic ecosystems, may be a result of low habitat diversity in the water column and resulting competitive pressure. The occurrence of the highest photosynthetic rates when Chl a is low, under some of the highest diversities, suggests a more efficient use of irradiance under low biomass–high diversity conditions. Results suggest that this increased efficiency is not explained by potential reductions in nutrient limitation and intraspecific competition under lower biomasses and may be a result of niche complementarity.